Strengthening the metal-support interaction over Pt/SiO2-TiO(OH)2 by defect engineering for efficient dehydrogenation of dodecahydro-N-ethylcarbazole. (15th February 2023) - Yang, Zhuwei; Gong, Xiang; Li, Linsen; Jiang, Zhao; Zhang, Riguang; Fang, Tao
Graphical abstract: Highlights: 2.5 wt% Pt/SiO2 -TiO(OH)2 shows the highest catalytic performance compared with the other catalysts. A small amount of TiO(OH)2 component is found to play a major role in the dehydrogenation reaction. The enhanced oxygen vacancy concentration strengthens the SMSI effect between Pt and SiO2 -TiO(OH)2 . The strengthened SMSI effect changes the electronic structure of Pt optimizing d-band center to accelerate reaction. Abstract: Liquid organic hydrogen carriers (LOHC) are considered as the promising candidates for large-scale hydrogen storage. The N -ethylcarbazole/dodecahydro- N -ethylcarbazole (NECZ/12H-NECZ) system has received increasing attention due to its excellent comprehensive properties in the hydrogen storage candidates. In this work, the Pt/SiO2 -TiO(OH)2 catalysts are synthesized and show good activity, selectivity and stability for 12H-NECZ dehydrogenation reaction. Among them, the 2.5 wt% Pt/SiO2 -TiO(OH)2 catalyst shows the best dehydrogenation performance with 5.75 wt% H2 release amount and 98 % selectivity of NECZ. Combined with XRD, HRTEM, ATR-FTIR, XPS and EPR analysis, it is found that the oxygen vacancy concentration in Pt/SiO2 -TiO(OH)2 is significantly enhanced due to the formation of Si-O-Ti species compared with Pt/SiO2 and Pt/TiO(OH)2, which strengthens the SMSI (strong metal-supporting interaction) effect between metal Pt and support SiO2 -TiO(OH)2 . The optimized d-band center of catalyst is beneficial for accelerating the sluggish kinetics of the rate-limiting step of the whole dehydrogenation reaction. Furthermore, compared with the results by replacing SiO2 with Al2 O3 or CeO2, it is indicated that the introduction of oxides mainly plays the role of regulating the surface electronic state of TiO(OH)2 and increasing the oxygen vacancy concentration.